Identity in Accordance with the Contents of the American Deal of the Century - Abu Hazeem, Tareq; Al-Assaf, Jamal (Dirasat: Human and Social Sciences, 2022)
The study aims to investigate the degree of appreciation by the academic elites in the Jordanian society to the challenges of national identity according to the contents of the American Deal of the Century in accordance with nationality and age variables. The study members are from the academic elites in the Jordanian society. They were chosen by the purposeful method, and their number is (320) researchers and thinkers. The study tool is developed to achieve its objectives after reviewing previous studies, political, and social literature. The results of the study indicate that the degree of appreciation by the academic elites in the Jordanian society to the challenges of national identity according to the contents of the American Deal of the Century is high. Also, the existence of statistically significant differences for the tool as a whole depending on the nationality variable. Whereas, there are no statistically significant differences for the tool as a whole depending on the age variable. In light of the results of the study, the study comes out with a set of recommendations.